2019
DOI: 10.3390/f10121088
|View full text |Cite
|
Sign up to set email alerts
|

Identification and Expression of NAC Transcription Factors of Vaccinium corymbosum L. in Response to Drought Stress

Abstract: Research Highlights: Phenotypic changes and expression profiles, phylogeny, conserved motifs, and expression correlations of NAC (NAM, ATAF1, ATAF2 and CUC2) transcription factors (TFs) in blueberry genome were detected under drought stress, and the expression patterns and functions of 12 NACs were analyzed. Background and Objectives: Blueberry is an important shrub species with a high level of flavonoids in fruit, which are implicated in a broad range of health benefits. However, the molecular mechanism of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
14
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 9 publications
(15 citation statements)
references
References 70 publications
1
14
0
Order By: Relevance
“…These results verified the complete network of photoprotective mechanism in OE lines [38]. Recent studies revealed that the inhibition of light energy conversion could produce more excess excitation energy and promote the accumulation of ROS in plant [39]. In grape, Sun et al found that the inhibition of Alternative oxidase (AOX) pathway increased the accumulation of H 2 O 2 , thus resulting in the photoinhibition under heat conditions [40].…”
Section: Pwnac11 Positively Regulates Drought Resistance In Transgenic Arabidopsissupporting
confidence: 63%
“…These results verified the complete network of photoprotective mechanism in OE lines [38]. Recent studies revealed that the inhibition of light energy conversion could produce more excess excitation energy and promote the accumulation of ROS in plant [39]. In grape, Sun et al found that the inhibition of Alternative oxidase (AOX) pathway increased the accumulation of H 2 O 2 , thus resulting in the photoinhibition under heat conditions [40].…”
Section: Pwnac11 Positively Regulates Drought Resistance In Transgenic Arabidopsissupporting
confidence: 63%
“…In this study, the 102 VcMYB DEGs were assigned to 16 GO categories (Additional file 6 and Additional file 7). The results showed that 102 DEGs participated in the biological process (38), cellular component (7) and molecular function (21). The "metabolic process" gene (11) was the dominant category in the biological process category accounting for 16.92 %.…”
Section: Go Annotation Analysis Of Vcmyb Degsmentioning
confidence: 99%
“…Under the condition of greenhouse, three treatments of plants were applied by withholding irrigation 15 days after transplanting. The soil water content (SWC) reached the predetermined levels without water for 10, 20 and 40 days, respectively [7]. The gravimetric method was employed to control the SWC [72].…”
Section: Plant Materials and Experimental Treatmentsmentioning
confidence: 99%
See 2 more Smart Citations